Epistemological Criticism of Scott Siraj al-Haqq Kugle's Ethical ‎Hermeneutics: A Review of Ulum al-Tafsir on the Interpretation of the ‎Story of the People of Lot - Ridwan Ridwan; Rusydi Am; Faizin Faizin (Jurnal Ulunnuha, 2025)
The debate on homosexuality in Islam extends beyond normative legal conclusions to encompass the epistemological legitimacy of the interpretive methods employed. Scott Siraj al-Haqq Kugle is among the prominent scholars who advance an ethical–progressive hermeneutical approach to Qur’anic passages concerning the people of Lot, emphasizing moral reasoning, historical context, and social justice. This article aims to provide an epistemological critique of Kugle’s hermeneutics from the perspective of classical ulūm al-tafsīr. Rather than advocating for or rejecting sexual inclusivity per se, the study seeks to examine the methodological coherence, epistemic authority, and interpretive limits of modern ethical hermeneutics within the Islamic exegetical tradition. In contrast to Mobeen Vaid’s study, which primarily offers a normative refutation of attempts to legitimize homosexual acts in Islam and critiques Kugle’s Qur’anic revisionism, this research does not treat QS al-A‘rāf [7]:80–84 as the principal material object of interpretation. Instead, the passage functions as a test case for assessing the broader ethical-hermeneutical framework employed by Kugle. Employing a qualitative methodology based on library research and critical–hermeneutical analysis, the article examines Kugle’s major works and systematically compares them with foundational principles of classical tafsir, including the authority of sanad, the interpretive role of Companions and tābiʿūn, the structure of istidlāl, and the epistemological relationship between ethics and law in Qur’anic interpretation. The findings indicate that Kugle’s hermeneutical approach privileges universal ethical norms and modern historical consciousness but remains insufficiently integrated with the epistemological instruments of classical tafsir. This methodological gap risks reducing the normative force of the Qur’anic text and weakening the authority of the Islamic interpretive tradition. The article argues that the primary challenge in Kugle’s approach lies not merely in its ethical conclusions, but in its underlying epistemological and methodological foundations. Accordingly, this study contributes to contemporary Qur’anic hermeneutics by critically delineating the limits of modern ethical interpretation and proposing a more balanced methodological integration between contemporary ethical reasoning and the disciplines of traditional Islamic exegesis